Functional Axis of PDE5/cGMP Mediates Timosaponin-AIII-Elicited Growth Suppression of Glioblastoma U87MG Cells - Ya-Fang Liao; Hui-Jun Pan; Nuerziba Abudurezeke; Chun-Lu Yuan; Yan-Li Yuan; Shu-Da Zhao; Dan-Dan Zhang; Shuang Huang (Molecules, 2023)
Glioblastoma (GBM) is the most aggressive brain tumor, with high mortality. Timosaponin AIII (TIA), a steroidal saponin isolated from the medicinal plant Anemarrhena asphodeloides Bge., has been shown to possess anticancer properties in various cancer types. However, the effect of TIA on GBM is unknown. In this study, we reveal that TIA not only inhibited U87MG in vitro cell growth but also in vivo tumor development. Moreover, we found that the cause of TIA-induced cell growth suppression was apoptosis. When seeking to uncover antitumor mechanisms of TIA, we found that TIA diminished the expression of cGMP-specific phosphodiesterase 5(PDE5) while elevating the levels of guanylate cyclases (sGCβ), cellular cGMP, and phosphorylation of VASPser239. Following the knockdown of PDE5, PDE5 inhibitor tadalafil and cGMP analog 8-Bro-cGMP both inhibited cell growth and inactivated β-catenin; we reason that TIA elicited an antitumor effect by suppressing PDE5, leading to the activation of the cGMP signaling pathway, which, in turn, impeded β-catenin expression. As β-catenin is key for cell growth and survival in GBM, this study suggests that TIA elicits its anti-tumorigenic effect by interfering with β-catenin function through the activation of a PDE5/cGMP functional axis.